2015
DOI: 10.6061/clinics/2015(04)12
|View full text |Cite
|
Sign up to set email alerts
|

Annual national direct and indirect cost estimates of the prevention and treatment of cervical cancer in Brazil

Abstract: OBJECTIVE:To estimate the annual direct and indirect costs of the prevention and treatment of cervical cancer in Brazil.METHODS:This cost description study used a "gross-costing" methodology and adopted the health system and societal perspectives. The estimates were grouped into sets of procedures performed in phases of cervical cancer care: the screening, diagnosis and treatment of precancerous lesions and the treatment of cervical cancer. The costs were estimated for the public and private health systems, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 17 publications
1
17
0
10
Order By: Relevance
“…In 2012, cervical cancer was the fourth most common type of cancer among women worldwide with an estimated 528,000 new cases and 266,000 deaths; 87% of deaths occurred in low and middle-income countries [ 3 ]. Treatment costs for cervical cancer remain high with low survival probabilities due to late diagnosis in many countries [ 4 , 5 ]. HPV vaccines offer an approach for primary prevention of HPV infection that can eventually reduce the health and economic burden of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, cervical cancer was the fourth most common type of cancer among women worldwide with an estimated 528,000 new cases and 266,000 deaths; 87% of deaths occurred in low and middle-income countries [ 3 ]. Treatment costs for cervical cancer remain high with low survival probabilities due to late diagnosis in many countries [ 4 , 5 ]. HPV vaccines offer an approach for primary prevention of HPV infection that can eventually reduce the health and economic burden of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies found large discrepancies between RHIS data and an estimated disease burden in populations or highlighted the lack of service provision. A few studies also used RHIS data to describe specific programs [ 60 – 64 ], conduct impact evaluations (non-programmatic) [ 65 68 ], and estimate costs [ 69 , 70 ]. Most of the studies investigated a communicable disease (95%), of which malaria was most studied health condition (24%).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these studies found large discrepancies between RHIS data and an estimated disease burden in populations or highlighted the lack of service provision. A few studies also used RHIS data to describe speci c programs [60][61][62][63][64] , conduct impact evaluations (non-programmatic) [65][66][67][68] , and estimate costs 69,70 .…”
Section: Resultsmentioning
confidence: 99%